Analysis of Gracilaria Sp. Seaweed Waste Substitution in Ration on the Quality of Local Duck Eggs - Agil Maulidina; Andi Batari K. Jabbar; Muhammad Sah; Nurmiani Syam; Saptriani Putri Ridwan; Hikmah Maulifiah Zaim; Nirmala (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
Gracilaria sp. is type of seaweed with abundant availability but has not been optimally utilized. This type of seaweed contains nutrients are polysaccharides, fiber, vitamins (B12, C, and E), protein, amino acids, and fatty acids, indicating its potential as an alternative feed ingredient for poultry, especially laying ducks. This study aimed to evaluate the effects of substitution Gracilaria sp. seweed meal waste with different levels in ration on the duck eggs quality. The parameters measured were egg weight, yolk index, white index, haugh unit, yolk weight, and shell thickness. The experimental design used was a completely randomized design consisting of 4 treatments and 3 replications. The dietary treatments were P0: ration without Gracilaria sp. seaweed meal waste substitution. (control), P1: ration + 5% Gracilaria sp. seaweed meal waste, P2: ration + 10% Gracilaria sp. seaweed meal waste, and P3: ration + 15% Gracilaria sp. seaweed meal waste. The results showed that the addition of Gracilaria sp. seaweed meal waste in the ration up to 15% did not significantly effect (P>0.05) on the quality of local duck eggs. However, treatment P1 (ration + 5% Gracilaria sp. seaweed meal waste) showed exhibited numerically higher values in egg weight, yolk weight, yolk index, and shell thickness. The conclusion is the use of Gracilaria sp. seaweed meal waste has the potential as an alternative feed in laying duck rations with an optimal usage level of 5% without decrease egg quality.